WOMEN LABOR MIGRATION IN ASIA: MOTHER MIGRATION AND ITS IMPACTS ON LEFT-BEHIND CHILDREN - Meirina Ayumi Malamassam (Research Centre for Population, Indonesian Institute of Sciences, 2014)
Female labor migration has been a prominent feature of labor migration in Asia since 1980s. Indonesia, along with Philippines and Sri Lanka, have been major sending countries of this type of migrants. Since the majority of the migrants are go abroad unaccompanied, this situation resulted in changes of left-behind family arrangement. Changes majorly apply to caregiving arrangement of left-behind children. Based on the research by PPK-LIPI in 2011, this article discuss theimpacts of mother migration on left-behind children in Indramayu, West Java and their adaptation process to such situation. In order to get more comprehensive understanding of this issue, particularly in Asian context, this article also discuss similar cases on Philippines and Sri Lanka by reviewing related literatures.It appears that mothers’ migration has a significant impact on left-behind children’s development process. While there are different extent of the impacts, the children’s communication with migrate mothers play an important role on the coping strategies of the children. In community context, the opinion of the children’s surroundings in regards to mothers’ absence in their daily lives would also determine the children’s acceptance of their mother migration.Keywords: mother migration, left-behind children, impact, women labor migration